Additional PD-1 inhibitor improves complete response to induction chemotherapy in locally advanced nasopharyngeal carcinoma - Yu, Yi-Feng; Lu, Guan-Zhong; Wang, Run-Jie; Song, Yu-Kun; Wu, San-Gang (Frontiers in Immunology, 2024)
Purpose: To investigate the treatment response and toxicity of the combination of induction chemotherapy (IC) and PD-1 inhibitor in locally advanced nasopharyngeal carcinoma (LANPC).Methods: Patients with stage III-IVA NPC who received IC or IC + PD-1 inhibitor were included. The chi-square test and multivariate logistic regression analysis were used for statistical analysis.Results: A total of 225 patients were identified, including 193 (85.8%) and 32 (14.2%) who received IC alone and IC + PD-1 inhibitor, respectively. The addition of PD-1 inhibitor to IC significantly improved the tumor response than those treated with IC alone. The complete response (CR), partial response, stable disease, and progressive disease rates of 4.7% vs. 31.3%, 69.4% vs. 62.5%, 24.9% vs. 6.3%, and 1.0% vs. 0% in patients receiving IC alone and IC + PD-1 inhibitor, respectively (P<0.001). The results of the multivariate logistic regression showed that receiving PD-1 inhibitor was an independent predictor influencing the CR rate of patients (odds ratio 9.814, P<0.001).The most common toxicity by using IC and PD-1 inhibitor was hematological toxicity.In terms of non-hematological toxicity, 7 (21.9%) patients experienced thyroid dysfunction and all of them were hyperthyroidism. No grade 5 toxicities were found.In those who received IC and PD-1 inhibitor, the one-year locoregional recurrence-free survival, distant metastasis-free survival, disease-free survival, and overall survival were 100%, 96.9%, 96.9%, and 100%, respectively.The addition of PD-1 inhibitor to IC has promise as an effective treatment approach for LANPC. More studies are expected to provide further insights into the optimal use of this treatment strategy, paving the way for more personalized and effective treatment options for patients with LANPC.